Conditional higher order moments in metal asset returns. Issue 1 (2nd January 2016) - Cochran, Steven J.; Mansur, Iqbal; Odusami, Babatunde
Abstract : This study examines the role of higher order moments in the returns of four important metals, aluminium, copper, gold and silver, using the asymmetric GARCH (AGARCH) model with a conditional skewed generalized- t (SGT) distribution. Implications of higher order moments in metal returns are evaluated by comparing the performances of conditional value-at-risk measures obtained from the AGARCH models with SGT distributions to those obtained from the AGARCH models with normal and student- t distributions. With the exception of gold, the AGARCH model with the SGT distribution appears to have the best fit for all metals examined.